Técnicas de regeneración pulpar en dientes inmaduros. revisión bibliográfica - Vega Molina, Dilan Alexander (2024)
Introduction: Pulp regeneration is presented as a prominent innovation in endodontic practice, providing a treatment option for the revitalization of immature teeth affected by pulp necrosis. This therapeutic approach not only seeks to promote the resumption of root growth and thickening of the tooth walls, but also to improve the structural viability of the tooth involved. Objective: To analyze the different techniques used for pulp regeneration in immature teeth and the materials used. Materials and methods: An exhaustive search was carried out in databases of clinical and scientific relevance, such as PubMed, Scopus, and Web of Science. Specific search strategies were designed to facilitate the identification and retrieval of studies relevant to pulp regeneration techniques. Results: From a preliminary set of 157 studies, 18 met the inclusion criteria and were selected for detailed analysis. The selection was based on the relevance of the studies to pulp regeneration techniques in immature teeth, following the guidelines established by the PRISMA method. Conclusion: Pulp regeneration techniques in immature teeth proved to be a promising therapeutic approach, with a variability of success rates ranging from 88% to 93%. The techniques identified include the use of temporary antibacterial pastes, application of growth factors, and the use of three-dimensional matrices to guide tissue growth. Despite the encouraging results, significant variations in treatment protocols, materials used, and evaluation criteria were observed among the studies analyzed.